Zastosowanie demograficznych modeli wielokrotnego ubytku w kalkulacji składek w ubezpieczeniach na życie - Wieteska, Stanisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Life probability parameter survival or death are very important in calculation premium in life insurance. Among this problems very often is included probability connected with reason of death. These parameters name is decrements.In this article there is a definition of decrements, force of mortality, central rate death and at the end, there were given examples of their application.There are also main mathematic formulas, witch should be used in actuarial practice. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 348-356